Nanofiber Composite for Improved Water Retention and Dendrites Suppression in Flexible Zinc‐Air Batteries. Issue 39 (24th August 2021) - Chen, Zhaoyang; Yang, Xing; Li, Wenqiong; Liang, Xiaoguang; Guo, Jiaming; Li, Haihan; He, Yun; Kim, Yoonseob
Abstract: Water loss of the gel polymer electrolytes (GPEs) and dendrites growth on Zn anode are overriding obstacles to applying flexible zinc‐air batteries (ZABs) for wearable electronic devices. Nearly all previous efforts aim at developing novel GPEs with enhanced water retention and therefore elongate their lifespan. Herein, a facile interface engineering strategy is proposed to retard the water loss of GPE from the half‐open structured air cathode. In detail, the poly(ethylene vinyl acetate)/carbon powder (PEVA‐C) nanofiber composite interface layer with features of hydrophobicity, high conductivity, air permeability, and flexibility are prepared on the carbon cloth and set up between the GPE and electrode. The as‐assembled ZAB with simple alkaline PVA GPE exhibits an impressive cycle life of 230 h, which outperforms ZAB without the PEVA‐C nanofibers interface layer by 14 times. Additionally, the growth of Zn dendrites can be suppressed due to the tardy water loss of GPE. Abstract : The prepared poly(ethylene vinyl acetate)/carbon powder nanofiber composite interface layer on carbon cloth features hydrophobicity, high conductivity, air permeability, and flexibility, resulting in tardy water loss of gel polymer electrolyte and suppression of the Zn dendrites' growth. The assembled zinc‐air battery with a simple alkaline polyelectrolyte system exhibits remarkable cycle life of 230 h.